2016
DOI: 10.5539/ijbm.v11n3p119
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Students’ Choice for MBA Program in Kuwait Universities

Abstract: The attempt is made in this study to identify students’ motives and reasons behind enrolling in a MBA program offered by universities operating in Kuwait. It also explores criterion used to select the program. To achieve these objectives, data were collected through a well-designed and structured questionnaire and pre-testing was carried out to examine the efficiency of the instrument. The study showed that the main reasons behind selecting the MBA program by students are to satisfy their personal concerns and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The literature search found few published studies regarding information sources consulted by aspiring postgraduate students. The review suggested the following as the most commonly consulted sources for information by prospective postgraduate students: social media such as Facebook, LinkedIn, and Instagram (Galan, Lawley, & Clements, 2015); Internet (AL-Mutairi & Saeid, 2016), and friends and family (AL-Mutairi & Saeid, 2016). Other information sources include print media (AL-Mutairi & Saeid, 2016); university agents (Moogan, 2018); and alumni, campus visit, and education expos (AL-Mutairi & Saeid, 2016).…”
Section: Sources Of Competitive Advantagementioning
confidence: 99%
“…The literature search found few published studies regarding information sources consulted by aspiring postgraduate students. The review suggested the following as the most commonly consulted sources for information by prospective postgraduate students: social media such as Facebook, LinkedIn, and Instagram (Galan, Lawley, & Clements, 2015); Internet (AL-Mutairi & Saeid, 2016), and friends and family (AL-Mutairi & Saeid, 2016). Other information sources include print media (AL-Mutairi & Saeid, 2016); university agents (Moogan, 2018); and alumni, campus visit, and education expos (AL-Mutairi & Saeid, 2016).…”
Section: Sources Of Competitive Advantagementioning
confidence: 99%
“…In regard to the third group of motives to enrol in a postgraduate programme, academic motives appeared as significant motives (AL-Mutairi and Saeid, 2016; Keane, 2016; Leech and Haug, 2016; Mokhtar, 2012; Passyn and Diriker, 2011; Wiegerová, 2016). This group refers to the desire of students to acquire further knowledge in their fields and to improve their mental abilities as a whole.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second group of motives to enrol and pursue a postgraduate programme is the self-motives (AL-Mutairi and Saeid, 2016; Dailey et al , 2006; Epstein et al , 2013; Golovushkina and Milligan, 2012; Leech and Haug, 2016; Mokhtar, 2012; Ng et al , 2008; Passyn and Diriker, 2011; Wiegerová, 2016). Most of the studies on self-motives suggested the feelings of satisfaction and accomplishment as the most salient self-motives.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…schooling days (Lichtenberger & George-Jackson, 2013b) and its impact is more suitable for females (Martin & Dixon, 2016); however, Gray & Daugherty (2004) noticed that schools are not fully promising for urging students into engineering education. (AL-Mutairi & Saeid, 2016) (Khanna et al, 2014) while selecting one major among various available engineering majors (Jarvie-Eggart et al, 2020). Students presently studying are the actual teamsters that can fetch prospective students of the same cultural and social experiences they belong to into institute by their motivational interaction (Malgwi et al, 2005a).…”
Section: Human In Uencementioning
confidence: 99%